Design, Modeling, and Control of a Brushless Permanent Magnet Motor for Electric Vehicles - Khlifi, Mohamed Arbi; Ben Slimene, Marwa (Engineering, Technology & Applied Science Research, 2024)
Electric Vehicles (EVs) are becoming more and more common. In addition to their ecological advantages, EVs have demonstrated their efficiency in curtailing travel expenses by transitioning from gasoline to electricity, which is significantly less costly. This study proposes a Brushless Permanent Magnet Motor (BPMM) design for EVs, models the influence of average and ripple torque, and evaluates its efficiency compared to other designs. The validity of the proposed design was supported by simulation results.